Dual channel routing scheme in ad hoc networks - WANG Qing-hui1; GONG Chang-qing1; WANG Guang-xing1 (Tongxin xuebao)
By improving the capacity of ad hoc networks by using multiple channel interfaces,a dual channel routing（DCR）scheme was introduced that proactively maintains all nodes’ location information based on periodic exchanges of location information in one channel.Based on the information,shortest path algorithm was used to find route to destination.Then,source transmitted data packet in another channel.DCR is a hybrid proactive/reactive scheme.Because there is no interference between two channels,the results of simulation show that the scheme can improve networks performance.